A PENGEMBANGAN MEDIA MYSTERY BOX UNTUK MENINGKATKAN KETERAMPILAN BERHITUNG PADA PESERTA DIDIK KELAS I SEKOLAH DASAR - Saryandi, Saryandi; Yuhana, Yuyu; Vivi Yandari, Indhira Asih; Alamsyah, Trian Pamungkas (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
Mystery Box is a media for learning numeracy that is currently popular and suitable for use in learning numeracy skills. This research aims to determine the process of developing the Mystery Box media, to determine the feasibility of the learning media and students' responses to the Mystery Box media and to determine the improvement in numeracy skills in class I elementary school students. This research was conducted at Az-Zahra Elementary School. Data collection techniques in this research are interviews, observation, questionnaires and documentation. The research and development method uses a research and development research design by Borg & Gall which was developed by Sugiono, namely potential and problems, data collection, product design, product validation, design revision, and product trials (limited trials). Based on validation by material experts, they obtained an average percentage score of 79% in the